Solution Interpolation Method for Highly Oscillating Hyperbolic Equations - Pilwon Kim; Chang Hyeong Lee (Journal of Applied Mathematics)
This paper deals with a novel numerical scheme for hyperbolic equations with rapidly changing terms. We are especially interested in the quasilinear equation ut+aux=f(x)u+g(x)un and the wave equation utt=f(x)uxx that have a highly oscillating term like f(x)=sin(x/ε),   ε≪1. It also applies to the equations involving rapidly changing or even discontinuous coefficients. The method is based on the solution interpolation and the underlying idea is to establish a numerical scheme by interpolating numerical data with a parameterized solution of the equation. While the constructed numerical schemes retain the same stability condition, they carry both quantitatively and qualitatively better performances than the standard method.